2015 IEEE International Conference on Robotics and Automation (ICRA) 2015
DOI: 10.1109/icra.2015.7139892
|View full text |Cite
|
Sign up to set email alerts
|

Estimating joint movements from observed EMG signals with multiple electrodes under sensor failure situations toward safe assistive robot control

Abstract: In this paper, we propose an estimation method of human joint movements from measured EMG signals for assistive robot control. We focus on how to estimate joint movements using multiple EMG electrodes even under sensor failure situations. In real world applications, EMG sensor electrodes might become disconnected or detached from skin surfaces. If we consider EMG-based robot control for assistive robots, such sensor failures lead to significant errors in the estimation of user joint movements. To cope with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Many classic machine learning approaches have also been used: support vector machine (SVM) [9], [10], self-organizing map (SOM) [11], k-nearest neighbors (kNN) [12], etc. To detect anomalies from time-series signals, researchers have also used hidden Markov models [3] or Kalman filters [13].…”
Section: Related Workmentioning
confidence: 99%
“…Many classic machine learning approaches have also been used: support vector machine (SVM) [9], [10], self-organizing map (SOM) [11], k-nearest neighbors (kNN) [12], etc. To detect anomalies from time-series signals, researchers have also used hidden Markov models [3] or Kalman filters [13].…”
Section: Related Workmentioning
confidence: 99%
“…As introduced above, EMG measurements have been used by a number of research groups to estimate joint torques, also in the context of robotic support with AAN control algorithms [31], [32]. For example, by using EMG measurement data as an input for computational models of the musculoskeletal system, the actual joint torque may be estimated, which may then be used to derive the deficient joint torque [33].…”
Section: A Related Workmentioning
confidence: 99%
“…This tendency was seen in other subjects as well. Therefore, it was shown that the estimated goal label ŷ can be used as a user's motor goal calculated by (3). In this study, based on these results, we set the user's motor goal for the 1 m goal shot as w 1 = 1 − w 2 and the 3 m goal shot as w 2 = 1 1+exp(−aŷ−b) .…”
Section: B Feature Extraction and Weight Determination Based On Plsmentioning
confidence: 99%
“…Because of the recent progress in robotics technologies, wearable robots, such as exoskeleton robots, are expected to physically interact with and assist humans in their activities. As proof-of-principle, the hand exoskeleton [1], [2], and upper and lower-body exoskeleton robots [3], [4], [5] have been studied. For these applications, the use of surface electromyography (EMG) can be a possible approach to intuitively control the robots by estimating the user's movement intention [6], [7].…”
Section: Introductionmentioning
confidence: 99%